An urban techno-economic analysis and modelling for Turkey - UYAR, TANAY SIDKI (ELSEVIER, 2021)
The energy profile of a city, with all of the relevant details about production and consumption phases, is a significant part of its sustainability rating. Therefore, municipalities have initiated the development of Sustainable Energy Action Plans as a key document to introduce the respective course of actions in order to define the technology adaptation process, identify the principal sources of CO2 emissions and their respective reduction potentials for the designated target years. A complete energy-strategy plan is required to handle the financial, technical, and environmental dimensions, not just for the country, but also for cities. As a powerful energy model generator among the energy planning and optimization tools, TIMES utilizes the energy, economy, and environmental parameters simultaneously. This paper aims to oversee and indicate the possible implications of 2023 energy targets of Turkey in a city-level energy modeling. In this perspective, the city of Burdur is selected as the target to implement the designated solar energy policy targets. With this paper, nationwide official targets are evaluated for a city level by calculating long-term effects and costs to the system. A total of 5000 MW of solar energy utilization target of Turkey has been reduced to the urban level for Burdur, depending on its share of solar energy, and then applied as an alternative scenario on the energy model developed for this analysis. The results show that the solar share of the total installed capacity of Burdur city will reach 49% while tripling the solarbased electricity generation in its energy mix.